(untitled) (e-Journal of Linguistics, 2019)
Mental clause, as a grammatical realization used to express experience of our consciousness of the world, is commonly found in the text of meditation. This type of text is written to persuade people to act in a particular way as suggested by the speaker or writer. This research is aimed at exploring how the mental clause in Indonesian text is re-contextualized to convey the same meaning in English. The source language text is a text of meditation entitled Butir-Butir Kebijaksanaan: Titian Hidup Sehat dengan Meditasi Bio-Energi Ratu Bagus (Ida Pandita Mpu Nabe Parama Daksa Natha Ratu Bagus, 2012) and the target language text is its translation entitled Pearls of Wisdom: The Path of a Healthy Life with Ratu Bagus Bio-Energy Meditation (Stacey, 2014). Knowing that translation is re-contextualization (House, 2015) and using Systemic Functional Linguistics (Halliday & Matthiessen, 2014) and translation strategies (Malone, 1988) as the main theories, this study focuses on the directions of the translation of the mental clause from Indonesian into English and on the translation strategies leading to the directions. The research result shows that the mental clause of the Indonesian text can be rendered into various clause types, including mental clause and non-mental clause. It can also be rendered into a form of nominalization. The strategies which condition the directions include the strategies of equation, reordering, diffusion and condensation.